Special aluminum electrolytic capacitor for block chain computer and preparation method thereof

By using a specific electrolyte solution and an improved anode foil melting liquid in an aluminum electrolytic capacitor, combined with heating impregnation treatment and surfactant ratio, the problem of poor electrochemical stability of existing aluminum electrolytic capacitors at high temperatures is solved, and higher ripple current capability and charge and discharge characteristics are achieved, extending the service life of the capacitor.

CN119742182APending Publication Date: 2025-04-01ZHAOQING BERYL ELECTRONICS TECH

Patent Information

Application Number
CN202411772270.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing aluminum electrolytic capacitors have poor electrochemical stability at high temperatures, and their ripple current resistance and charge and discharge characteristics are limited, which cannot meet the high-temperature operation needs of blockchain computer equipment.

Method used

The specific electrolyte and the improved anode foil are used to improve the permeability and viscosity reduction of the electrolyte through heating and impregnation treatment, and the structure and performance of the capacitor are optimized by combining the ratio of surfactant and additives.

Benefits of technology

It improves the high temperature stability, ripple current capability and charge and discharge characteristics of aluminum electrolytic capacitors, extends the service life of the capacitor and improves its reliability in blockchain computers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005170539020000051
    Figure BDA0005170539020000051
  • Figure BDA0005170539020000071
    Figure BDA0005170539020000071
  • Figure BDA0005170539020000081
    Figure BDA0005170539020000081
Patent Text Reader

Abstract

The invention discloses an aluminum electrolytic capacitor special for a block chain computer and a preparation method of the aluminum electrolytic capacitor, and the preparation method comprises the following steps: S1, a positive guide pin and a negative guide pin are respectively riveted on an anode foil and a cathode foil, and a formation liquid used by the anode foil is composed of boric acid, citric acid mixed acid and maleic acid; s2, interposing electrolytic paper between the anode foil and the cathode foil, and winding to form a core package; s3, carrying out heating and impregnation on the wound core package in an electrolyte; s4, assembling the core package, the aluminum shell and the sealing rubber plug; s5, an aging step; the electrolyte consists of the following components in percentage by mass: 43-60% of a solvent, 30-42% of a solute, 3-10% of an additive and 1-5% of a surfactant, the surfactant is composed of ammonium chromate, alkyl phosphate, a silicic acid compound and polyacrylamide. The aluminum electrolytic capacitor prepared by the method provided by the invention can keep good performance and long service life in a high-temperature and high-pressure working environment, and is very suitable for a block chain computer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and more specifically, to an aluminum electrolytic capacitor dedicated to a blockchain computer and a preparation method thereof. Background Art

[0002] Blockchain computer refers to a computer system built using blockchain technology. It combines new application modes of computer technologies such as distributed data storage, peer-to-peer transmission, consensus mechanism, encryption algorithm, etc. The computing devices of existing blockchain network systems are generally directly installed on the computer motherboard. However, since the computer motherboard will have a high heat after working for a long time, the heat dissipation of the temperature in the chassis will weaken, which will cause the working temperature of the computing devices of the blockchain network system fixed on the computer motherboard to rise sharply. As a result, not only the operating efficiency of the computing devices of the blockchain network system is low, but also the aging speed of the computing devices of the blockchain network system will be accelerated, so as to reduce the service life of the computing devices of the blockchain network system. This puts forward higher and higher requirements on aluminum electrolytic capacitors used for computer power supply filtering. First of all, it is required to have a large capacity, a high working voltage, a small size, and be able to withstand a large ripple current. The capacitor should be used continuously for a long time, and it is best to ensure that the computer can work continuously, so a long life is also required.

[0003] Although the current foreign domestic high-voltage long-life aluminum electrolytic capacitor has a mature technology level of 10,000 hours of normal working time at 105°C, for example, China Invention Application 202310144062.9 discloses a method for preparing an ultra-high voltage aluminum electrolytic capacitor for air conditioning, comprising the following steps: S1: cutting the raw material to the required width; S2: winding the cut raw material into a core by a winding machine; S3: drying the core; S4: immersing the dried core in a liquid electrolyte; the electrolyte contains additives, including PVA103 and HA-01, PVA103 accounts for 1-5% of the mass percentage of the electrolyte, and HA-01 accounts for 1-10% of the mass percentage of the electrolyte; S5: assembling the aluminum shell, the rubber plug and the impregnated core to make a capacitor; S6: putting an insulating sleeve on the outside of the aluminum shell; S7: performing high-temperature pressurized aging on the sleeved capacitor; S8: measuring the sorting parameters of the aged capacitor to screen out good products. However, since the working electrolyte system used is relatively simple, the working electrolyte has poor high-temperature electrochemical stability, limited ripple current resistance and charge and discharge characteristics, and is easily decomposed under high-temperature reactions, the product generates high heat and has large temperature rise changes, which cannot meet the development needs of blockchain computer equipment.

[0004] Therefore, the development and production of high-quality, high-quality aluminum electrolytic capacitors used in blockchain computers is becoming more and more urgent. Summary of the invention

[0005] Based on this, it is necessary to provide an aluminum electrolytic capacitor dedicated to blockchain computers and a preparation method thereof to address the above technical problems.

[0006] In order to solve the above technical problems, the present invention provides an aluminum electrolytic capacitor dedicated to a blockchain computer and a preparation method thereof, which adopts the following technical solution:

[0007] The first aspect of the present invention provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, comprising the following steps: S1, a positive electrode guide pin and a negative electrode guide pin are riveted to an anode foil and a cathode foil respectively, and a chemical forming liquid used for the anode foil is composed of a mixed acid of boric acid, citric acid and maleic acid;

[0008] S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package;

[0009] S3, heating and impregnating the wound core package in an electrolyte;

[0010] S4, assembling the core package, the aluminum shell and the sealing rubber plug;

[0011] S5, aging step;

[0012] The electrolyte is composed of the following components by mass percentage: 43-60% solvent, 30-42% solute, 3-10% additive, and 1-5% surfactant;

[0013] The surfactant is composed of ammonium chromate, alkyl phosphate, silicic acid compound and polyacrylamine;

[0014] The aluminum electrolytic capacitors prepared by S1 to S5 are used in blockchain computers.

[0015] Furthermore, the solvent is composed of the following components by mass percentage: 40-55% of n-butanol, 20-30% of propylene glycol, 12-20% of diethylene glycol monomethyl ether, and 5-10% of diethylene glycol monoethyl ether.

[0016] Furthermore, the solute is composed of the following components by mass percentage: 30-45% citric acid, 22-35% succinic acid, 12-20% ammonium formate, 8-12% nitrilotriacetic acid, and 2-6% ethylene carbonate.

[0017] Furthermore, the additive is composed of the following components by mass percentage: 33-47% mannitol, 25-35% ammonium hypophosphite, 15-22% diammonium ethylenediaminetetraacetate, and 3-10% polypropylene alcohol.

[0018] Furthermore, the surfactant is composed of the following components by mass percentage: 33-45% of ammonium chromate, 20-33% of alkyl phosphate, 15-25% of silicic acid compound, and 5-10% of polyacrylamine.

[0019] Furthermore, the heating impregnation temperature in S3 is 65-75° C., and the impregnation treatment time is 170-190 min.

[0020] Furthermore, the electrolytic paper described in S2 is a composite fiber of wood pulp and cotton pulp.

[0021] Furthermore, the impregnation temperature is the liquid temperature after the electrolyte is injected into the impregnation tank.

[0022] Furthermore, the hot charging temperature of the S5 aging step is 90-100°C.

[0023] The second aspect of the present invention proposes an aluminum electrolytic capacitor dedicated to a blockchain computer prepared by the above method.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The preparation method of the aluminum electrolytic capacitor dedicated to the blockchain computer proposed in the present invention, on the one hand, uses an anode foil liquefied by boric acid, citric acid mixed acid and maleic acid to improve the structure and performance of the anode foil oxide film, shorten the boost time after hydration, and improve the hydration resistance of the anode oxide film. In addition, when combined with the specific electrolyte of the invention, the oxide film layer on the uneven surface of the aluminum foil can be quickly processed, the effective area of ​​the electrode plate can be increased, the capacity attenuation can be reduced, the withstand voltage of the aluminum foil can be stabilized, and the product reliability can be improved. On the other hand, the specific electrolyte provided by the present invention has high oxidation formation efficiency, stable voltage at high temperature, and the ability to quickly repair oxide film defects. It is a working electrolyte with stable comprehensive performance and improved ripple current capacity, which solves the technical problem that the ripple current will decrease with the increase of temperature, resulting in high internal heat of the product, thereby causing the electrolyte in the liquid capacitor to volatilize and fail, so as to reduce the gas pressure inside the capacitor and prevent corrosion from causing capacitor failure.

[0026] The preparation method of the aluminum electrolytic capacitor dedicated to the blockchain computer proposed in the present invention increases the impregnation temperature of the core package and reduces the viscosity of the electrolyte after heating, so that the electrolyte can penetrate into the core package more easily, greatly shortens the impregnation time, improves the impregnation efficiency and consistency, and improves the performance of the capacitor. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the solutions in the present application or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 : This is the state of the test sample No. 5 in Comparative Example 3 of the present invention Figure 1 ;

[0029] Figure 2 : This is the state of the test sample No. 5 in Comparative Example 3 of the present invention Figure 1 . DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0031] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0032] Example 1

[0033] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which includes the following steps:

[0034] S1, the positive electrode guide pin and the negative electrode guide pin are riveted to the anode foil and the cathode foil respectively, and the anode foil uses a chemical solution composed of a mixed acid of boric acid, citric acid and maleic acid;

[0035] S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package, wherein the electrolytic paper is a composite fiber of wood pulp and cotton pulp;

[0036] S3, heating and impregnating the wound core package in an electrolyte, the impregnation temperature is 70° C., and the impregnation treatment time is 180 min;

[0037] The impregnation temperature refers to the liquid temperature after the electrolyte is injected into the impregnation tank;

[0038] S4, assembling the core package, the aluminum shell and the sealing rubber plug;

[0039] S5, aging, the hot charging temperature of the aging step is 95°C;

[0040] The electrolyte is composed of the following components by mass percentage: 52% solvent, 38% solute, 7% additive, and 3% surfactant;

[0041] The solvent is composed of the following components by mass percentage: 48% of n-butanol, 26% of propylene glycol, 16% of diethylene glycol monomethyl ether, and 10% of diethylene glycol monoethyl ether;

[0042] The solute is composed of the following components by mass percentage: 40% citric acid, 28% succinic acid, 18% ammonium formate, 10% nitrilotriacetic acid, and 4% ethylene carbonate;

[0043] The additive is composed of the following ingredients by mass percentage: 40% mannitol, 32% ammonium hypophosphite, 20% diammonium ethylenediaminetetraacetate, and 8% polypropylene alcohol;

[0044] The surfactant is composed of the following components by mass percentage: 43% of ammonium chromate, 30% of alkyl phosphate, 22% of silicic acid compound and 5% of polyacrylamine.

[0045] The 20 electrolytic capacitors prepared according to Example 1 were tested for capacitor performance. The results are shown in Table 1.

[0046] Table 1: Performance test results of 20 electrolytic capacitors prepared according to Example 1

[0047]

[0048] Example 2

[0049] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which includes the following steps:

[0050] S1, the positive electrode guide pin and the negative electrode guide pin are riveted to the anode foil and the cathode foil respectively, and the anode foil uses a chemical solution composed of a mixed acid of boric acid, citric acid and maleic acid;

[0051] S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package, wherein the electrolytic paper is a composite fiber of wood pulp and cotton pulp;

[0052] S3, heating and impregnating the wound core package in an electrolyte, the impregnation temperature is 65° C., and the impregnation treatment time is 170 min;

[0053] The temperature during impregnation refers to the liquid temperature after the electrolyte is injected into the impregnation tank;

[0054] S4, assembling the core package, the aluminum shell and the sealing rubber plug;

[0055] S5, aging, the hot charging temperature of the aging step is 90°C;

[0056] The electrolyte is composed of the following components by mass percentage: 43% solvent, 42% solute, 10% additive, and 5% surfactant;

[0057] The solvent is composed of the following components by mass percentage: 40% n-butanol, 30% propylene glycol, 20% diethylene glycol monomethyl ether, and 10% diethylene glycol monoethyl ether;

[0058] The solute is composed of the following components by mass percentage: 30% citric acid, 35% succinic acid, 17% ammonium formate, 12% nitrilotriacetic acid, and 6% ethylene carbonate;

[0059] The additive is composed of the following ingredients by mass percentage: 33% mannitol, 35% ammonium hypophosphite, 22% diammonium ethylenediaminetetraacetate, and 10% polypropylene alcohol;

[0060] The surfactant is composed of the following components by mass percentage: 35% ammonium chromate, 33% alkyl phosphate, 25% silicic acid compound, and 7% polyacrylamine;

[0061] The 20 electrolytic capacitors prepared according to Example 2 were tested for capacitor performance. The results are shown in Table 2.

[0062] Table 2: Performance test results of 20 electrolytic capacitors prepared according to Example 2

[0063]

[0064] Example 3

[0065] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which includes the following steps:

[0066] S1, the positive electrode guide pin and the negative electrode guide pin are riveted to the anode foil and the cathode foil respectively, and the anode foil uses a chemical solution composed of a mixed acid of boric acid, citric acid and maleic acid;

[0067] S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package, wherein the electrolytic paper is a composite fiber of wood pulp and cotton pulp;

[0068] S3, heating and impregnating the wound core package in an electrolyte, the impregnation temperature is 75°C, the impregnation treatment time is 190 min, and the temperature during the impregnation refers to the liquid temperature after the electrolyte is injected into the impregnation tank;

[0069] S4, assembling the core package, the aluminum shell and the sealing rubber plug;

[0070] S5, aging, the hot charging temperature of the aging step is 100°C;

[0071] The electrolyte is composed of the following components by mass percentage: 60% solvent, 30% solute, 9% additive, and 1% surfactant;

[0072] The solvent is composed of the following components by mass percentage: 55% n-butanol, 20% propylene glycol, 20% diethylene glycol monomethyl ether, and 5% diethylene glycol monoethyl ether;

[0073] The solute is composed of the following components by mass percentage: 45% citric acid, 22% succinic acid, 20% ammonium formate, 11% nitrilotriacetic acid, and 2% ethylene carbonate;

[0074] The additive is composed of the following ingredients by mass percentage: 43% mannitol, 25% ammonium hypophosphite, 22% diammonium ethylenediaminetetraacetate, and 10% polypropylene alcohol;

[0075] The surfactant is composed of the following components by mass percentage: 45% of ammonium chromate, 20% of alkyl phosphate, 25% of silicic acid compound, and 10% of polyacrylamine;

[0076] The 20 electrolytic capacitors prepared according to Example 3 were tested for capacitor performance. The results are shown in Table 3.

[0077] Table 3: Performance test results of 20 electrolytic capacitors prepared according to Example 3

[0078]

[0079] Example 4

[0080] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which includes the following steps:

[0081] S1, the positive electrode guide pin and the negative electrode guide pin are riveted to the anode foil and the cathode foil respectively, and the anode foil uses a chemical solution composed of a mixed acid of boric acid, citric acid and maleic acid;

[0082] S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package, wherein the electrolytic paper is a composite fiber of wood pulp and cotton pulp;

[0083] S3, heating and impregnating the wound core package in an electrolyte, the impregnation temperature is 70° C., and the impregnation treatment time is 180 min;

[0084] The temperature during impregnation refers to the liquid temperature after the electrolyte is injected into the impregnation tank;

[0085] S4, assembling the core package, the aluminum shell and the sealing rubber plug;

[0086] S5, aging, the hot charging temperature of the aging step is 90°C;

[0087] The electrolyte is composed of the following components by mass percentage: 56% solvent, 38% solute, 3% additive, and 3% surfactant;

[0088] The solvent is composed of the following components by mass percentage: 52% of n-butanol, 29% of propylene glycol, 12% of diethylene glycol monomethyl ether, and 7% of diethylene glycol monoethyl ether;

[0089] The solute is composed of the following components by mass percentage: 43% citric acid, 34% succinic acid, 12% ammonium formate, 8% nitrilotriacetic acid, and 3% ethylene carbonate;

[0090] The additive is composed of the following ingredients by mass percentage: 47% mannitol, 35% ammonium hypophosphite, 15% diammonium ethylenediaminetetraacetate, and 3% polypropylene alcohol;

[0091] The surfactant is composed of the following components by mass percentage: ammonium chromate 44%, alkyl phosphate 32%, silicic acid compound 15%, polyacrylamine 9%;

[0092] The 20 electrolytic capacitors prepared according to Example 4 were tested for capacitor performance. The results are shown in Table 4.

[0093] Table 4: Performance test results of 20 electrolytic capacitors prepared according to Example 4

[0094]

[0095] Comparative Example 1

[0096] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that diethylene glycol monoethyl ether is not added to the solvent of the electrolyte.

[0097] The 20 electrolytic capacitors prepared according to Comparative Example 1 were tested for capacitor performance, and the results are shown in Table 5.

[0098] Table 5: Performance test results of 20 electrolytic capacitors prepared according to comparative example 1

[0099]

[0100] Compared with the test results of Example 1, the test products of this comparative example all showed the phenomenon of slight bulging of the aluminum shell after the high-temperature corrugation life test, and the leakage current LC value after the charge and discharge test exceeded the test value in Example 1 by more than 10 times. This is because in Example 1, diethylene glycol monoethyl ether was added to dissolve with the main solvent propylene glycol, which increased the concentration of free ions in the electrolyte, enhanced the conductivity of the solution, and increased the number of free ions electrolyzed, thereby increasing the conductivity and reducing the viscosity, making it easy for the electrolyte to fully contact the oxide film layer on the uneven surface of the corrosion-treated aluminum foil, and at the same time improving the oxidation formation efficiency of the electrolyte, which is helpful to form a mixed solvent with stable comprehensive performance, so that the electrolyte can still maintain a high stability after the life test and the charge and discharge test.

[0101] Comparative Example 2

[0102] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that ethylene carbonate is not added to the solute of the electrolyte.

[0103] The 20 electrolytic capacitors prepared according to Comparative Example 2 were tested for capacitor performance, and the results are shown in Table 6.

[0104] Table 6: Performance test results of 20 electrolytic capacitors prepared according to comparative example 2

[0105]

[0106] In this comparative example, ethylene carbonate is not added to the solute of the electrolyte, because nitrilotriacetic acid will precipitate at room temperature due to its low solubility, affecting the performance of the electrolyte. From the test results, it can be seen that after the high-temperature ripple life test and the charge and discharge test, the DF value, ESR value and LC value of the test sample are greatly increased compared with Example 1. This is because ethylene carbonate is added in Example 1 and blended with nitrilotriacetic acid, which is easy to separate from the reaction mixture, so that it will decompose when heated, and the solubility is no longer restricted, thereby increasing the pH of the solution and having a very strong complexing ability, thereby improving the high temperature and high pressure resistance of the electrolyte, reducing the thermal motion speed of charged ions under the action of the electric field, and reducing the energy of thermal breakdown of charged ions; the ripple current does not decrease with increasing temperature, resulting in high internal heating of the product.

[0107] Comparative Example 3

[0108] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that polypropylene alcohol is not added to the additive of the electrolyte.

[0109] The 20 electrolytic capacitors prepared according to Comparative Example 3 were tested for capacitor performance, and the results are shown in Table 7.

[0110] Table 7: Performance test results of 20 electrolytic capacitors prepared according to comparative example 3

[0111]

[0112] In this comparative example, polypropylene alcohol was not added, and the life performance of the aluminum electrolytic capacitor was poor. Figure 1 and 2 As shown, the guide pin of test sample No. 5 is corroded and broken, and the aluminum foil is corroded. This is because polypropylene alcohol and diammonium ethylenediaminetetraacetic acid work synergistically and have a fast enough dispersion speed to generate less heat when used at high currents, improve ripple current capability, and solve the problem that free chloride ions are highly active and have strong penetration ability, and can easily penetrate into the product through the capacitor seal, causing the aluminum foil and leads to corrosion and leading to capacitor failure.

[0113] Comparative Example 4

[0114] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that no polyacrylamine is added to the surfactant of the electrolyte.

[0115] The 20 electrolytic capacitors prepared according to Comparative Example 4 were tested for capacitor performance, and the results are shown in Table 8.

[0116] Table 8: Performance test results of 20 electrolytic capacitors prepared according to Comparative Example 4

[0117]

[0118] Compared with the test results of this comparative example and Example 1, the test samples all showed aluminum shell bulging after the high-temperature corrugation life test, and some of the test samples also showed aluminum shell bulging after the charge and discharge test and the LC value increased significantly. The polyacrylamide added in Example 1 can improve the active adsorption capacity and can combine with the active defect sites of the anode foil through chemical adsorption and electrochemical adsorption, so that the repair ability and efficiency of the oxide film defects on the anode foil are effectively enhanced, and it is deposited on the surface of the aluminum foil to protect and prevent the aluminum foil from hydration and reduce the amount of hydrogen generated during the working process of the electrolytic capacitor, so as to reduce the gas pressure inside the capacitor and prevent the capacitor from failing due to excessive pressure during use.

[0119] Comparative Example 5

[0120] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that the anode foil in step S1 is liquefied by conventional boric acid.

[0121] The 20 electrolytic capacitors prepared according to Comparative Example 5 were tested for capacitor performance, and the results are shown in Table 9.

[0122] Table 9: Performance test results of 20 electrolytic capacitors prepared according to comparative example 5

[0123]

[0124] Compared with this comparative example, the anode foil formed by the boric acid, citric acid mixed acid and maleic acid system liquefaction used in Example 1 can improve the structure and performance of the anode foil oxide film, shorten the boost time after hydration, and improve the hydration resistance of the anode oxide film. When matched with the electrolyte, it can quickly process the oxide film layer on the uneven surface of the aluminum foil, increase the effective area of ​​the electrode plate, reduce the capacity attenuation, stabilize the withstand voltage of the aluminum foil, and improve the product reliability. All performances of the tested products are better than those of this comparative example.

[0125] Comparative Example 6

[0126] This embodiment provides a method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, which differs from Embodiment 1 in that the impregnation temperature in step S3 is 50°C.

[0127] The 20 electrolytic capacitors prepared according to Comparative Example 6 were subjected to capacitor performance tests, and the results are shown in Table 10.

[0128] Table 10: Performance test results of 20 electrolytic capacitors prepared according to Comparative Example 6

[0129]

[0130] In this comparative example, after the high-temperature corrugation life test, the test samples all showed slight bulging of the aluminum shell, and after the charge and discharge test, a small number of test samples also showed bulging of the aluminum shell. In Example 1, by increasing the temperature of the impregnating electrolyte, the viscosity of the electrolyte is reduced after heating, making it easier for the electrolyte to penetrate into the core package. On the one hand, the impregnation efficiency and consistency are improved, and on the other hand, the impregnation time can be greatly shortened to improve the performance of the capacitor.

[0131] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer, characterized in that: The following steps are involved: S1, the positive electrode guide pin and the negative electrode guide pin are riveted to the anode foil and the cathode foil respectively, and the anode foil uses a chemical solution composed of a mixed acid of boric acid, citric acid and maleic acid; S2, inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; S3, heating and impregnating the wound core package in an electrolyte; S4, assembling the core package, the aluminum shell and the sealing rubber plug; S5, aging step; The electrolyte is composed of the following components by mass percentage: 43-60% solvent, 30-42% solute, 3-10% additive, and 1-5% surfactant; The surfactant is composed of ammonium chromate, alkyl phosphate, silicic acid compound and polyacrylamine; The aluminum electrolytic capacitors prepared by S1 to S5 are used in blockchain computers.

2. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 1, characterized in that: The solvent is composed of the following components by mass percentage: 40-55% of n-butanol, 20-30% of propylene glycol, 12-20% of diethylene glycol monomethyl ether and 5-10% of diethylene glycol monoethyl ether.

3. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 2, characterized in that: The solute is composed of the following components by mass percentage: 30-45% of citric acid, 22-35% of succinic acid, 12-20% of ammonium formate, 8-12% of nitrilotriacetic acid, and 2-6% of ethylene carbonate.

4. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 3, characterized in that: The additive is composed of the following components by mass percentage: 33-47% of mannitol, 25-35% of ammonium hypophosphite, 15-22% of diammonium ethylenediaminetetraacetate, and 3-10% of polypropylene alcohol.

5. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 4, characterized in that: The surfactant is composed of the following components by mass percentage: 33-45% of ammonium chromate, 20-33% of alkyl phosphate, 15-25% of silicic acid compound and 5-10% of polyacrylamine.

6. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 1, characterized in that: The heating and impregnation temperature in S3 is 65-75° C., and the impregnation treatment time is 170-190 min.

7. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 1, characterized in that: The electrolytic paper described in S2 is a composite fiber of wood pulp and cotton pulp.

8. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 6, characterized in that: The impregnation temperature is the liquid temperature after the electrolyte is injected into the impregnation tank.

9. The method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claim 1, characterized in that: The hot charging temperature of the S5 aging step is 90-100°C.

10. An aluminum electrolytic capacitor prepared according to the method for preparing an aluminum electrolytic capacitor dedicated to a blockchain computer according to claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of ultrahigh-voltage aluminum electrolytic capacitor for air conditioner

    CN116825544A

Cited By

  • Special aluminum electrolytic capacitor for electric tool and preparation method thereof

    CN120527158A